2011
DOI: 10.5732/cjc.30.0407
|View full text |Cite
|
Sign up to set email alerts
|

Identification of plasma microRNA-21 as a biomarker for early detection and chemosensitivity of non-small cell lung cancer

Abstract: Studies have shown cell鄄 free microRNA (miRNA) circulating in the serum and plasma with specific expression in cancer, indicating the potential of using miRNAs as biomarkers for cancer diagnosis and therapy. This study was to investigate whether plasma miRNA鄄 21 (miR鄄 21) can be used as a biomarker for the early detection of non-small cell lung cancer (NSCLC) and to explore its association with clinicopathologic features and sensitivity to platinum鄄 based chemotherapy. We used real鄄 time RT鄄 PCR to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 0 publications
2
54
1
2
Order By: Relevance
“…miR21 was shown to be several folds lower in patients with a partial response and to be a biomarker for early diagnosis of NSCLC. Plasma miR-21 could predict sensitivity to platinum based chemotherapy as well (Wei et al, 2011).…”
Section: 2167 Lung Cancer Detection By Screening For Circulating Mirmentioning
confidence: 99%
“…miR21 was shown to be several folds lower in patients with a partial response and to be a biomarker for early diagnosis of NSCLC. Plasma miR-21 could predict sensitivity to platinum based chemotherapy as well (Wei et al, 2011).…”
Section: 2167 Lung Cancer Detection By Screening For Circulating Mirmentioning
confidence: 99%
“…Jeong et al found the expression of let-7a miRNA is lower in NSCLC tissues than in normal lung tissues (24). Blood miR-21 was found up-regulated in pancreatic cancer (38,39) as well as NSCLC (29,40), so several miRNAs are dysregulated as a phenomenon of cancer rather than due to a specific cancer. Different expression of miRNAs has been reported in human NSCLC, fewer studies to date have examined whether circulating miRNA levels could be useful in differentiating NSCLC from control groups.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-16 was proven as one of commonly used internal control genes to determine expressions of miRNAs as shown in previous work (25,26,46). In our included studies, three papers used miR-16 as internal control genes to normalize miRNA level (25,26,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma miR-21 expression may correlate with sensitivity to chemotherapy too. NSCLC patients who underwent 2 to 3 cycles of platinum-based therapy and reached partial response or stable disease effect had higher miR-21 expression compared with patients who had progression of the disease after treatment (p=0.049) [47].…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%